Factors affecting reproductive performance and estimates of genetic parameters of litter size in Horro sheep - Abegaz, Solomon; Duguma, G.; Negussie, E.; Gelmesa, U.; Terefe, F.; Rege, J.E.O. (Cambridge University Press, 2002)
Conception, lambing rate and litter size were studied on data from a flock of Horro sheep in Ethiopia from 1878 to 1997. The CATMOD and GLM procedures of SAS were used for the analysis of these traits. A sire, direct additive genetic and a repeatability animal model were employed to obtain estimates of heritability and repeatability for litter size. The results obtained showed that year of mating, age and weight of ewes at mating and number of previous parities had significantly (P < 0.01) affected the rate of conception and lambing while weight of rams at mating has shown no significant effect (P > 0.05). An increase in both conception and lambing rates was observed with the increase in weight of ewes up to about 36 kg and declined thereafter. Ewes which previously had no or one parity had lower conception and lambing rates compared with ewes in later parities. However, a decline in both conception and lambing rates was also observed in old ewes. Year of lambing, parity and weight of ewes at mating had a highly significant (P < 0.01) effect on litter size. The overall mean litter size in the flock was 1.34 with annual means ranging from 1.18 to 1.55. Litter size increased with parity from 1.26 in primiparous ewes to 1.44 for ewes of parities five and above. With respect to weight of ewes at mating, litter size increased by 2.5% for each kg increase in weight at mating. The estimates of direct heritability (h2) for litter size were 0.17, 0.11 and 0.06 under the sire, direct animal and repeatability models, respectively. Repeatability was estimated to be 0.12. Since heritability and repeatability estimates of litter size are low, genetic improvement by selection may not bring sizeable impact in increasing litter size. Therefore flock management for optimal age structure and optimal weight of ewes at mating should receive due consideration to improve rates of conception, lambing and litter size in Horro sheep.